Relationship between principals’ leadership attributes and school effectiveness in Niger state secondary schools, Nigeria - Bagobiri, Garba (2015)
Principals’ leadership has been a part of discussion on the effectiveness of school for the past decades, based on the assumption that no school can success without effective leadership of the principal. This resulted to the various researches on principals’ leadership and school effectiveness worldwide. Contemporarily, majority of principals cannot meet up with the mandated proficiency levels of student performance in Nigeria. The objective of this survey research is to determine the relationship between the principals’ leadership attributes and school effectiveness in Niger state secondary schools, Nigeria. This is a quantitative research, survey method and utilizes Leader Attributes Inventory (LAI) and School Effectiveness Index (SEI) as the instruments. The study involved 230 secondary schools, comprising the senior and assistant senior masters in Niger state secondary schools, which gives the total population (N) of 460. 136 schools were chosen and simple random sampling technique was used to select the sample size (S) of 272. SPSS (V20) was used to run the analysis. Descriptive analysis was used to determine the level of the principals’ leadership attributes and school effectiveness. Correlation analysis was used to determine the relationship between the principals’ leadership attributes and regression analysis was used to determine the contribution of the principals’ leadership attributes to school effectiveness. The level of principals’ leadership attributes is moderate (mean =3.54, sd = 0.68). The level of school effectiveness is also at a moderate level (mean = 3.50, sd = .83). The correlation analysis shows that there is high positive significant relationship between the dimension of principals’ leadership attributes and school effectiveness, management skills (r= .676, p = .01), personal characteristics (r = .616, p = .01), and social skills and characteristics (r = .686, p = .01). Regression analysis shows that, two dimensions of principals’ leadership attributes have significantly contributed to school effectiveness, management skills (β = .356, t = 4.188, p = .000) and social skills and characteristics (β = .340, t = 3.483, p = .001). It is concluded that, principals' leadership attributes in Niger state secondary schools as found out in the study are still at the moderate level and needs further improvement. Principals should possess effective leadership attributes. They play a vital and critical role in directing the schools, and teaching and learning towards school effectiveness. Therefore, there are needs to develop programs with a substantial package to improve the leadership attributes of the principals systematically and continuously so as to prepare them for the multifaceted roles towards school effectiveness in the future.